A contribuição de Lima Barreto para o entendimento da crítica educacional brasileira do início do século XX - Lopes, Silvana Fernandes [UNESP] (My University, 2010)
This study aims at enhancing the understanding of the educational criticism in the beginning of the twentieth century, focusing on the ideas of Lima Barreto. Before the emergence of the "educational professionals", educational thought was developed by publicists and writers involved in a fertile debate, the results of which became visible in literary and journalistic production. Through the analysis of articles, short texts published in the press, novels and short stories written by Lima Barreto, it’s possible to gather a specific concept of education, underlying his criticism and fictional characterization of school education, as well as an interesting sketch of the cultural profile of Brazilian society at the time. Either explicitly or implicitly, in their evaluative and theoretical references, the limits of the critical readings of the author, which are expressed in the contradiction between negation of the given conditions and their affirmation, unveil the historical aspects of social and educational thinking and criticism.

Este artigo procura ampliar a compreensão da crítica educacional do início do século XX, tomando como objeto de exame o pensamento social de Lima Barreto. Até a emergência dos “profissionais da educação”, o pensamento educacional era elaborado por publicistas e literatos, num fértil debate, cujos resultados apareciam na produção jornalística e literária. Por meio do exame de artigos, crônicas, romances e contos de Lima Barreto, é possível apreender uma determinada concepção educacional, subjacente às críticas e à caracterização ficcional da educação escolar, assim como um interessante esboço do perfil cultural da sociedade brasileira do período. Os limites nos quais esbarra a leitura crítica do autor, expressos na contradição entre a negação das condições dadas e a sua afirmação, explícita ou implícita, nos seus referenciais teóricos e valorativos, revelam o caráter histórico do pensamento e da crítica social e educacional.
Keywords: Brasil; Educação; Ensino Superior; Educação na Literatura; Brazil; Education; High Education; Education in Literature